Keadilan Gender dalam Undang-Undang Tenaga Kerja di Indonesia - Anis Faridatul Hasanah; Iza Hanifuddin (IJoIS: Indonesian Journal of Islamic Studies, 2021)
This study tries to analyze women's employment law in Indonesia. In this case, the analysis of the case in the forms of violation of labor rights against women and how they are protected according to the Manpower Act. Women workers have the right to work and earn an income for a decent living. Women have the same rights as men in choosing jobs that match their abilities and interests and are not respected without discrimination, which is also regulated in the law. The laws and regulations in Indonesia itself have undergone changes and changes that have taken place many times. Starting from the formation of laws in Indonesia, especially before the amendment to the 1945 Constitution, the enactment of Law Number 10 of 2004, and previously Law Number 12 of 2011. The types and rules of legislation regulated in Article 7 of Law No. The laws are as follows: the 1945 Constitution of the Republic of Indonesia, TAP MPR, Laws/Perpu, Government Regulations, Presidential Regulations, and Regional Regulations. Ratification, Promulgation, and Dissemination and promulgated by the state secretariat.